Unveiling the transformation and bioavailability of dissolved organic matter in contrasting hydrothermal vents using fluorescence EEM-PARAFAC. (15th March 2017) - Yang, Liyang; Zhuang, Wan-E; Chen, Chen-Tung Arthur; Wang, Bing-Jye; Kuo, Fu-Wen
Abstract: The submarine hydrothermal systems are extreme environments where active cycling of dissolved organic matter (DOM) may occur. However, little is known about the optical properties and bioavailability of hydrothermal DOM, which could provide valuable insights into its transformation processes and biogeochemical reactivity. The quantity, quality, and bioavailability of DOM were investigated for four very different hydrothermal vents east of Taiwan, using dissolved organic carbon (DOC), absorption spectroscopy, and fluorescence excitation-emission matrices-parallel factor analysis (EEM-PARAFAC). The DOC and absorption coefficient a 280 were both lower in the two hydrothermal vents off the Orchid Island and on the Green Island than in the surrounding seawater and the two vents off the Kueishantao Island, indicating effective removals of DOM in the former two hydrothermal systems owing to possible adsorption/co-precipitation and thermal degradation respectively. The four hydrothermal DOM showed notable differences in the absorption spectral slope S 275-295, humification index HIX, biological index BIX, EEM spectra, and the relative distributions of seven PARAFAC components. The results demonstrated a high diversity of chemical composition and transformation history of DOM under contrasting hydrothermal conditions. The little change in the hydrothermal DOC after 28-day microbial incubations indicated a low bioavailability of the bulk DOM, and different PARAFAC components showed contrasting bioavailability. The results have profound implications for understanding the biogeochemical cycling and environmental effects of hydrothermal DOM in the marine environments. Graphical abstract: Highlights: The diversity of hydrothermal DOM fluorescence is revealed for the first time by EEM-PARAFAC. The DOM has undergone different transformations in contrasting hydrothermal systems. The hydrothermal DOM has a low bioavailability as tested by DOC measurements and EEM-PARAFAC.